The idea of Meliorism in scientific creativity of Professor Maria Dudzikowa. Assumptions and one example - Józef Górniewicz (Studia z Teorii Wychowania)
The article discusses the idea of Meliorism present in the scientific autput of Professor Maria Dudzikowa. I analyze in detail the content of the book „On the difficult art. of self-creation”, seeling in the content references to the idea of Meliorism.